Beyond environmentalism: The geopolitical chess game behind Indonesia's mineral export bans and renewable energy transition - Kirana, Dhea Nur; Triantama, Febry (Masyarakat, Kebudayaan dan Politik, 2024)
The increase in human energy consumption and the serious effects of the dominance of fossil energy, especially limited supply and climate change, have an impact on changes in the global geopolitical order. As such, the adaptation carried out by Indonesia became an important step in ensuring national energy security amidst global challenges. This research highlights the urgency of accelerating the energy transition to renewable sources in Indonesia as part of the national strategy. Efforts to accelerate the energy transition are not only a response to global demands, but also as an effort to maintain energy security, environmental sustainability, and are an important geopolitical factor. This study uses mixed research methods, where the author carries out quantitative data processing and then juxtaposes it with qualitative processing and analysis. The analysis was carried out using the concept of resource geopolitics. This study found that abundant renewable resource capacity, downstream efforts by the government, reduced dependence on other countries, and increasingly mature energy transition readiness make Indonesia better prepared to face global geopolitical competition. This study concludes that accelerating the energy transition in Indonesia is not just a response to global demands, but is also a strategic step to increase energy security, disaster resilience and environmental resilience.